1999
DOI: 10.1002/(sici)1097-0185(19990201)254:2<181::aid-ar4>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic expression of a native chondroitin sulfate epitope reveals microheterogeneity of extracellular matrix organization in the embryonic chick heart

Abstract: TC2 is a novel monoclonal antibody produced by in vitro immunization of splenocytes with a peanut agglutinin-positive fraction from extracts of prechondrogenic micromass cultures of chick limb mesenchyme. ELISA results demonstrated TC2 reactivity with a native epitope on a glycosaminoglycan (GAG) enriched in chondroitin-4-sulfate and with multiple intact proteoglycans, but not with other GAGs tested. TC2 immunohistochemical reactivity was abolished by pretreatment of sections with chondroitinase AC or preadsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…Versican cleavage is presumably driven by versican-cleaving proteinases belonging to the ADAMTS and MMP family, although definitive studies of the expression of the complete repertoire of these proteases concomitant with OFT remodeling have yet to be performed. It is reasonable to propose that CNC cells mediate the proteolytic processing of versican, because changes in versican epitope detection (anti-DPEAAE-reactive and intact versican) correlate with CNC migration, and the fact that CNCs have been shown to express MMPs in the distal cardiac outlet (Alexander et al, 1997;Capehart et al, 1999;Zanin et al, 1999;Cai et al, 2000;Ratajska and Cleutjens, 2002). Consistent with the hypothesis that the G1 domain-containing fragment from versican acts to decrease myocardial cell-cell association required to initiate loss of distal myocardium, we showed that overexpression of the G1 domain accelerated the normal remodeling.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Versican cleavage is presumably driven by versican-cleaving proteinases belonging to the ADAMTS and MMP family, although definitive studies of the expression of the complete repertoire of these proteases concomitant with OFT remodeling have yet to be performed. It is reasonable to propose that CNC cells mediate the proteolytic processing of versican, because changes in versican epitope detection (anti-DPEAAE-reactive and intact versican) correlate with CNC migration, and the fact that CNCs have been shown to express MMPs in the distal cardiac outlet (Alexander et al, 1997;Capehart et al, 1999;Zanin et al, 1999;Cai et al, 2000;Ratajska and Cleutjens, 2002). Consistent with the hypothesis that the G1 domain-containing fragment from versican acts to decrease myocardial cell-cell association required to initiate loss of distal myocardium, we showed that overexpression of the G1 domain accelerated the normal remodeling.…”
Section: Discussionsupporting
confidence: 84%
“…Cardiac neural crest cells are at least one cell type in the developing OFT known to express MMP-2 (Cai et al, 2000). In the chick, versican expression is similar to the mouse, including a heterogeneity that the authors attribute to ECM proteolysis and led to the hypothesis that versi- can proteolysis was occurring during OFT development and may be initiated by the migration of cardiac neural crest cells (Capehart et al, 1999;Zanin et al, 1999). The observed correlation between versican cleavage and loss of the distal myocardium in the truncus raised the possibility that proteolytic cleavage of versican may not only inactivate versican activity but also generate fragments with activities distinct from the intact versican molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Because of possible structural modifications in an individual CS-GAG chain, antigenic determinants are generated that may be quite different from the repetitive backbone disaccharide structure. While the precise epitopes recognized by the d1C4 and TC2 antibodies utilized in this study are not known at this time, it is clear from previous studies (Capehart et al, 1997(Capehart et al, , 1999) that they reside on native CS-GAG chains enriched in either chondroitin-4-(TC2) or chondroitin-6-sulfate chains (d1C4). The CS-56 epitope may be found on both chondroitin-4-and -6-sulfate chains (Avnur and Geiger, 1984), suggesting strongly that the determinant recognized by this antibody is a structural variation of the usual backbone of CS-GAG chains.…”
Section: Discussionmentioning
confidence: 92%
“…Monoclonal antibody (MAb) TC2 was produced by in vitro immunization of naïve mouse splenocytes with a peanut agglutinin-positive fraction from prechondrogenic micromass cultures of chick limb mesenchyme (Capehart et al, 1999). It recognizes a native epitope on GAGs enriched in chondroitin-4-sulfate (bovine trachea; Sigma Chemical Co., St. Louis, MO).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation